EMBEDDED YOUNG STARS IN NORTHERN NGC 3372 - M. Tapia (Revista Mexicana de Astronomía y Astrofísica, 2011)
Deep narrow-band (Br at 2.17 ¿m and H2 at 2.12 ¿m) and broad-band (JHKs) near-infrared images are presented of the young regions Tr14-N4 and Car I. The observations were made with PANIC, attached to the Baade 6.5 m Magellan Telescope at Las Campanas Observatory. These were supplemented by archive Spitzer/IRAC images. Evidence is given of an embedded young compact cluster (r = 23'') of medium-to-low mass stars in Tr14-N4 but that includes at least one high mass protostar. Its properties are derived from the 1.2 to 11 ¿m photometry. The presence of outflows is evinced by knotty H2 emission near the edge of a cavity. We also presented updates of near-IR light-curves of Car I-136 and 125 embedded in the dark cloud associated with Car I.